Investigating the effects of vitamin D3 on clinical outcomes in newly diagnosed acute myeloid leukemia - Islam, Tahmidul; Alam, Sabrina; Khan, Naila Atik; Sharmin, Mahbuba; Akhtar, Nasrin; Islam, Kazi M. Kamrul; Sahera, Umme (International Journal of Research in Medical Sciences, 2025)
Background: Acute myeloid leukemia (AML) is a hematologic malignancy with poor prognosis. This study investigates the effects of vitamin D3 supplementation on clinical outcomes in newly diagnosed AML patients. To evaluate the impact of vitamin D3 on remission rates, overall survival and quality of life in AML patients. Methods: A hospital-based prospective cross-sectional study was conducted from January to December 2017, involving 145 newly diagnosed AML patients. Participants were divided into an intervention group receiving standard chemotherapy with oral vitamin D3 supplements and a control group receiving only chemotherapy. Clinical and biochemical assessments, including serum vitamin D3 levels, were performed at baseline and monthly for six months. Outcomes measured included remission rates, overall survival and quality of life scores. Results: The intervention group exhibited higher complete remission rates (69.4% vs. 56.2%, p=0.035) and improved overall survival (median survival of 18.2 months vs. 12.5 months, p=0.045). Quality of life scores were significantly better in the intervention group across multiple domains. Serum vitamin D3 levels increased significantly after three and six months of supplementation (p<0.001). The incidence of adverse effects was similar between groups. Conclusions: Vitamin D3 supplementation positively influences remission rates, overall survival and quality of life in newly diagnosed AML patients, suggesting its potential role as an adjunct therapy. Further large-scale, multi-center trials are needed to confirm these findings and explore the mechanisms behind the effects of vitamin D3 on AML.